Association between the synthetic vascular stent used for abdominal aortic aneurysm and generalized granuloma annulare - Han-Chi Tseng; Chih-Hung Lee (Wolters Kluwer Medknow Publications, 2015)
The etiology of granuloma annulare (GA) remains unknown, although several eliciting factors have been proposed. We herein present the case of an 81-year-old man who developed generalized erythematous annular plaques 6 months after engraftment of a vascular stent for abdominal aneurysm repair. Based on the diagnosis of generalized GA and the patient's age, we treated him with psoralens plus ultraviolet A therapy. The treatment response was good. This is the first report showing the association between vascular stent and generalized GA.